Modernization of the Target Design for Molybdenum Production - Kolmykov, V.Yu.; Zevyakin, A.S.; Fomin, R.V.; Sobolev, A.V. (KnE Engineering, 2018)
The following work is a comparative analysis of two target designs for Molybdenum-99 production. Important parameters for their usage are their thermal-hydraulic properties. The considered target designs can be used in a research reactor of basin type. The research channel, where the target is being installed, does not possess high static pressure; therefore, the target should not cause the coolant boiling during operation. The more fissile material in the target, the higher the expected isotope producing and at the same time the energy release. The main task of construction modernization of the target is to increase the production of the necessary radioisotope in the normal removal of heat from the walls of the target sleeve. Comparative analysis is carried out for targets of the cylindrical type.